1989
DOI: 10.1016/0092-8674(89)90765-4
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus induces a processing factor that stimulates poly(A) site usage

Abstract: Extracts from herpes simplex virus-infected cells and from mock-infected cells have been compared for their ability to process at RNA poly(A) sites in vitro. Nuclear extracts from infected cells contain an activity that increases processing efficiency specifically at a late herpes simplex virus poly(A) site. By contrast, a second virus poly(A) site is processed with equal efficiency by nuclear extracts from infected and mock-infected cells. Using precursor RNAs containing these two virus poly(A) sites in tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 60 publications
5
75
0
Order By: Relevance
“…A clue to the mechanism of ICP27 action was provided by Sandri-Goldin and Mendoza (53), who showed that ICP27 enhances expression of constructs bearing a synthetic and incomplete polyadenylation signal and inhibits expression of reporter genes bearing certain introns in transient-cotransfection assays. A complementary series of studies by Clements and colleagues demonstrated that HSV infection alters the specificity of the host polyadenylation machinery in an ICP27-dependent fashion, thereby allowing more efficient use of a subset of viral polyadenylation signals (31)(32)(33). These findings indicate that ICP27 modulates intranuclear processing of pre-mRNAs and suggest that it inhibits splicing of at least some intron-bearing transcripts (53).…”
Section: Herpes Simplex Virus (Hsv) Is a Large Enveloped Dna Virus Thmentioning
confidence: 98%
“…A clue to the mechanism of ICP27 action was provided by Sandri-Goldin and Mendoza (53), who showed that ICP27 enhances expression of constructs bearing a synthetic and incomplete polyadenylation signal and inhibits expression of reporter genes bearing certain introns in transient-cotransfection assays. A complementary series of studies by Clements and colleagues demonstrated that HSV infection alters the specificity of the host polyadenylation machinery in an ICP27-dependent fashion, thereby allowing more efficient use of a subset of viral polyadenylation signals (31)(32)(33). These findings indicate that ICP27 modulates intranuclear processing of pre-mRNAs and suggest that it inhibits splicing of at least some intron-bearing transcripts (53).…”
Section: Herpes Simplex Virus (Hsv) Is a Large Enveloped Dna Virus Thmentioning
confidence: 98%
“…ICP27 is the other essential regulatory IE gene (51), encoding a nuclear phosphoprotein which performs a number of diverse functions. These include repression of IE genes, control of the switch between E and L gene expression, and selection of transcriptional termination sites (40,42). ICP27 normally mediates the shutoff of host protein synthesis by sequestering snRNPs (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that transcriptional readthrough from the inserted sequences in vFJ7 and vFJl0 could lower the amount of USll mRNA available for translation either by production of anti-sense mRNA or transcriptional interference. Recently, it has been shown that readthrough of the HSV-2 IE5 poly(A) site sequences inserted into the virus vector occurs during lytic infection (McLauchlan et al, 1989). Thus, inefficient processing at the poly(A) sites of the CAT and flgalactosidase genes present in vFJ7 and vFJ10 could produce transcripts complementary to USll mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have used different promoters to drive CAT gene expression in vFJ7 and vFJ10, but protein-coding and mRNA 3' processing sequences can also be manipulated. Analysis of a CAT gene cassette, containing tandemly arranged poly(A) sites, inserted into 1802 has already facilitated identification of an HSV-induced factor which alters poly(A) site usage (McLauchlan et al, 1989). It is also relatively easy to construct alternative expression plasmids to use with these vectors.…”
Section: Discussionmentioning
confidence: 99%